SOCIAL SUPPORT FOR DIET COMMUNITIES IN SOCIAL MEDIA - Rizky Indah Cahyani; Helfi Agustin (Jurnal Kesehatan Masyarakat Andalas, 2020)
The number of users of social media in Indonesia has the potential to control global epidemiological problems including obesity. Does the group formed on social media, that consists of people who do not know each other, but because of the similarity of interest in losing weight, will help increase the motivation of the group members? The purpose of this study was to find a relationship between friend sup- port on social media with increased motivation in weight loss. This research is descriptive analytic, with cross sectional design. A sample of 110 people was selected using a purposive sampling technique. The research instrument was adopted from the Treatment Self-Regulation Questionnaire (TSRQ) and the Ballatine questionnaire. The results showed 88.2% of respondents were women, 85.5% were aged 20-40 years, most were housewives (50.9%), the period of joining groups on social media between 1-4 months (45.5%). About 49.1% of respon- dents felt strongly supported and motivated by members in fellow groups on social media. The statistical test results show that there is a relationship between social support and motivation for weight loss (pValue 0.019). This study shows that groups on social media can help maintain the motivation of their members to carry out a diet. It is recommended that health promotion personnel to use social media as an alternative to disseminating health program information.